PENGARUH KESADARAN WAJIB PAJAK, PELAYANAN FISKUS, DAN SANKSI PERPAJAKAN PADA KEMAUAN MENGIKUTI TAX AMNESTY - Arisa Dewi, Ni Putu; Noviari, Naniek (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
Tax Amnesty is elimination tax owed should not sanction tax administration and criminal sanctions in field of taxation, by way uncovering treasure and pay ransom money. Based on previous studies, shows the willingness to follow the tax amnesty is influenced by several factors taxpayer awareness, service tax authorities, and tax penalties. This study aimed to examine the effect of consciousness, service tax authorities, and tax penalties on the willingness to follow the tax amnesty step one. Samples in this study as many as 88 people registered taxpayers in North Badung STO and have followed the tax amnesty step one. The sample in this study was determined by convenience sampling method and slovin formula. Data collected using questionnaires and analysis technique is Multiple Linear Regression. Based on analysis awareness of the taxpayer, the service tax authorities, and tax penalties positive effect on the willingness to follow the tax amnesty step one.
Keywords: Tax Amnesty, Consciousness Taxpayer, Services Tax Authorities, Tax Penalties